The link between firm risk-taking and CEO power of listed firms on the Vietnamese stock market: the role of state ownership - Ngoc Thanh Tran; Thi Ngoc Dung Pham; Dien Duan Nguyen; Trung Kien Tran; Gia Quyen Phan; Tran Thai Ha Nguyen (Cogent Business & Management, 2024)
The Chief Executive Officer (CEO) is pivotal in firm governance and is tasked with policy implementation and maximizing shareholder benefit. However, predicting CEO behaviour remains challenging, especially when considering CEO power (CEOP). Hence, this study explores the link between CEOP and firm risk-taking (FRT) in selected firms on the stock market in Vietnam from 2010 to 2020. Utilizing the Entropy weight methodology, a CEOP index combines structural, ownership, and expert power indicators. The SYS-GMM approach mitigates potential endogeneity issues, revealing a positive correlation between CEOP and FRT. Interestingly, CEO risk aversion increases in state-owned firms' participants, suggesting heightened supervision. Moreover, each characteristic of the CEOP index uniquely influences FRT. The findings offer theoretical and practical insights for enhancing governance and supervision mechanisms to optimize stakeholder benefits.In business, avoiding all risks is impractical, and risk-taking endeavours can present growth opportunities. However, uncertainties from risks can impact financial performance, requiring corporations to demonstrate effective risk management. Decision-making and oversight of organizational activities are decided by the Chief Executive Officer (CEO). Hence, this study explores the interaction between CEO power and firm risk-taking in the context of Vietnam. Powerful CEOs tend to gravitate towards risks, but effective governance mechanisms and board independence can balance this tendency. The study recognizes the influential role of CEO power in shaping risk-taking behaviours and emphasizes the positive impact of state ownership. Balancing CEO empowerment with organizational supervision is crucial, and solutions include comprehensive risk assessments and clear operating frameworks. However, the study acknowledges limitations and recommends guidelines for a more comprehensive analysis in future research.
Keywords: G30; G32; M00; 650; CEO; ownership power; structural power; expert power; risk-taking; state ownership; Vietnam